Evaluasi Sensori dan Komposisi Gizi Wafel Substitusi Daun Pepaya Jepang (Cnidoscolus aconitifolius) sebagai Camilan Alternatif untuk Remaja Putri Anemia: Sensory Evaluation and Nutritional Composition of Waffle with Chaya Leaf (Cnidoscolus aconitifolius) Substitution as an Alternative Snacks for Adolescent Girls' Anemia - Arza, Putri Aulia; Yunianto, Andi Eka (Amerta Nutrition, 2025)
Background: Waffle is sweet food like cake but cooked differently, are a beloved snack for teenagers. Chaya is a leafy vegetable that is often consumed because it has a nutritional content that is beneficial for health and can be made into snacks such as waffles. Objectives: This study aimed to evaluate the nutritional and cyanide content of Chaya Leaf waffles using a selected formula as a potential solution for iron deficiency anemia in adolescents girls. Methods: Experimental research with a randomized complete design was conducted, varying the amount of Chaya Leaf are 0g, 25g, 50g, and 75g in waffle formulations. Sensory analysis is based on hedonic test results which are evaluated using SPSS version 25 analyzed using one-way ANOVA followed by DMRT (Duncan's Multiple Range Test) analysis, while proximate analysis was conducted following SNI 4305:2018 guidelines. Iron content was measured using atomic absorption spectrophotometry (SNI 01-2896-1998) and cyanide content using the acid titration method and the wet titration method based on SNI 4305:2018. Results: A hedonic test involving 30 semi-trained panelists favored formula F4, containing 75 g of Chaya Leaf, for its color (p-value<0.001), taste (p-value=0.001), and texture (p-value=0.019). In 100 g of waffle, water content was 54.15%, ash content was 2.06%, protein was 20.90%, fat was 12.16%, and carbohydrates were 63.67%. The iron content was 0.43 mg, and cyanide levels were found to be 0.919 mg/g. Conclusions: Formula F4 was preferred by panelists for its high iron content and safe cyanide levels, suggesting the potential of Chaya Leaf waffles as a nutritious snack for teenagers.